Онтологический подход к разработке интеллектуального ядра системы поддержки принятия решений в условиях чрезвычайных ситуаций - Лоцкина, Я. Г. (НТУ "ХПИ", 2014)
В статье проанализированы проблемы синтеза онтологической компоненты в составе интеллектуального ядра системы поддержки принятия решений, связанных с ликвидацией лесных пожаров. Изложен подход к разработке онтологической системы знаний о стратегии и тактике тушения лесных пожаров, лесной пирологии, а также о ресурсах для тушения, как совокупности трех предметных онтологий. Описан механизм реализации вывода на знаниях в среде онтологической системы. В основу подхода положена методология METHONTOLOGY.

The paper presents the analysis of the problem of synthesis of ontological component in the intelligent core of decision-making system related to woods fire fighting. The paper suggests an approach of ontological knowledge system development concerning the strategy and tactics of woods fire fighting, woods pyrology and necessary resources as a totality of three domain ontologies. The mechanism of knowledge-based inference in the ontological system is described. The basis of the approach is made by METHONTOLOGY approach. The process of ontology construction within this approach breaks down into a series of sub-processes to create an intermediate representation. In accordance with the proposed methodology, we first construct a glossary of terms, then concept classification trees and binary relations diagrams. The use of ontological approach to the creation of systems with artificial intelligence is promising in terms of improving the efficiency of decision-making in emergency situations, as well as conservation of intellectual capital of experts.
Ontological approach to the development of the intelligent core of decision support system under the conditions of emergent situations
Keywords: чрезвычайные ситуации; лесные пожары; тушение; система поддержки принятия решений; интеллектуальное ядро; онтология; онтологическая система; woods fire; decision support system; intelligent core; knowledge-based inference; ontology; ontological system